Investigation of Listeria species in chicken body parts and samples of water used for washing carcasses - Arslan, A; Gönülalan, Z; Dinçoglu, AH; Kök, F (Scientific Technical Research Council Turkey, 1999)
In this study chicken body pails (leg, neck, wing, breast) and samples of water for washing carcasses, obtained from a slaughterhouse in Elazig, were investigated in terms of listeria species. 20 samples were examined from each body part and carcass the water. L. monocytogenes, L. innocua and L. welshimeri were determined in 2, 7 and 4 leg samples; in 1, 3 and 5 wing samples and in 2, 5 and 4 water samples respectively. Only L. innocua was observed in 3 breast samples, L. monocytogenes and L. innocua were found in 3 and 2 leg samples respectively. In conclusion, it can be emphasized that the hygiene in the slaughterhouse was not adequate and that the personnel concerned with hygiene have to be educated.
Tavuk Karkas Kisimlari ve Karkas Yikama Sularinda Listeria Türlerinin İncelenmesi
Keywords: Listeria spp.; chicken; water